Persepsi dan Sikap ibu Hamil yang Menghadiri Antenatal Care Terhadap Infeksi Hepatitis B di Kepulauan Siompu Buton Selatan - marsyaban, Marsyaban; Anggorowati, Anggorowati; Dewi, Nur Setiawati (Universitas Tribhuwana Tunggadewi, 2023)
This research aims to know the knowledge and attitude of pregnant mothers about hepatitis in the Siompu District, South Buton District. The research uses descriptive qualitative design using thematic analysis, A semi-structured one-on-one interview through a face-to-face interview at Siompu. The interviews are recorded and transcribed word by word and then analyzed thematically. A total of 5 pregnant women participated in this study with a response rate of 93.7%, and each interview lasted 20 to 40 minutes. Five thematic categories were identified, while the participant’s psychological experiences were classified into five stages, namely (1) perception: the presence of anxiety; (2) attitudes: fears, and doubts about viruses; (3) transitional periods: complex and diverse psychological feelings; (4) adaptation period: self-adaptation and assistance from external support; and (5) reflection period: reflection on life and nature. The results study showed that the perception in pregnant women of hepatitis infection is still less, while pregnant mothers showed a very positive attitude towards therapy and immunization. So, it is highly recommended to raise awareness about the hepatitis virus, the ways of transmission, and possible treatment options.